Environment and the Inflammatory Bowel Diseases - Alexandra Frolkis; Levinus A Dieleman; Herman W Barkema; Remo Panaccione; Subrata Ghosh; Richard N Fedorak; Karen Madsen; Gilaad G Kaplan; on behalf of the Alberta IBD Consortium (Canadian Journal of Gastroenterology)
Inflammatory bowel diseases (IBD), which consists of Crohn disease and ulcerative colitis, are chronic inflammatory conditions of the gas-trointestinal tract. In genetically susceptible individuals, the interaction between environmental factors and normal intestinal commensal flora is believed to lead to an inappropriate immune response that results in chronic inflammation. The incidence of IBD have increased in the past century in developed and developing countries. The purpose of the present review is to summarize the current knowledge of the association between environmental risk factors and IBD. A number of environmental risk factors were investigated including smoking, hygiene, microorganisms, oral contraceptives, antibiotics, diet, breast-feeding, geographical factors, pollution and stress. Inconsistent findings among the studies highlight the complex pathogenesis of IBD. Additional studies are necessary to identify and elucidate the role of environmental factors in IBD etiology.